Characteristics and Outcomes of Patients with Invasive Pulmonary Aspergillosis and Respiratory Tract Aspergillus Colonization from a Tertiary University Hospital in Thailand - Pannathat Soontrapa (Journal of Fungi, 2022)
Positive culture for Aspergillus spp. from respiratory specimens needs to be interpreted together with relevant clinical conditions/settings to differentiate invasive infection from colonization. In this study, we aimed to investigate the association between positive culture for Aspergillus spp. from respiratory specimens and the presence of invasive pulmonary aspergillosis. Hospitalized patients with positive culture for Aspergillus spp. from any respiratory sample were retrospectively recruited. Patients were classified into two groups: those with invasive pulmonary aspergillosis and those with non-invasive aspergillosis/colonization. Two hundred and forty-one patients (48.1% male; mean age: 59.8 ± 14.5 years) were included. The most common Aspergillus spp. was A. fumigatus (21.0%). The most common underlying condition was chronic lung disease (23.7%), followed by solid tumor (22.4%). Myeloproliferative disease (aOR: 69.2, 95% CI: 2.4–1991.9), neutropenia ≥ 10 days (aOR: 31.8; 95% CI: 1.10–920.53), and corticosteroid treatment (aOR: 42.8, 95% CI: 6.5–281.3) were independent predictors of the invasive form. Chronic lung disease was independently inversely related to invasive form (OR: 0.04; 95% CI: 0.003–0.49). Serum galactomannan was positive in 69.2% of patients with invasive aspergillosis (OR: 25.9, 95% CI: 5.2–127.8). All inappropriately treated patients with invasive form died. In conclusion, positive culture for Aspergillus spp. from respiratory specimens with coexisting myeloproliferative disease, neutropenia ≥ 10 days, corticosteroid treatment, or positive serum galactomannan is highly suggestive of invasive pulmonary aspergillosis.